Copeptin, resistant hypertension and renal sympathetic denervation. (19th May 2017) - Schwerg, Marius; Slagman, Anna; Stangl, Karl; Stangl, Verena
Abstract: Background: Renal denervation is used as a treatment option for patients with resistant hypertension. But only a subgroup of patients benefits from renal sympathetic denervation (RDN). Biomarkers might be helpful to identify patients who respond to RDN. Copeptin as a surrogate for vasopressin levels is increased in hypertension and other cardiovascular diseases. This study aims to evaluate the effect of RDN on Copeptin and its prognostic value for response to RDN. Method and results: A total of 40 patients have been included in the study. The responder rate was 47.5% on 24 h ambulatory blood pressure measurements. The mean systolic 24 h blood pressure dropped from 152 ± 10 mmHg to 147 ± 17 mmHg ( p  = .044) in the six month follow up. The mean baseline level of Copeptin was 7.4 pmol/l (interquartile range 3.7–11.6) for responders and 8.4 pmol/l (interquartile range 5.7–11–8) for non-responders ( p  = .53). The Copeptin levels did not change over time after renal denervation. Conclusion: Baseline measurements of Copeptin in patients undergoing RDN for resistant hypertension have no predictive value for response to RDN. Despite lowering the blood pressure RDN has no influence on Copeptin levels in this short time follow up period.